(untitled) (Journal of International Studies, 2025)
The relationship between internal conflicts and national strategic decision-making remains complex and often unclear. This article examines the case of Xinjiang to explore the intricate connections between ethnic conflicts, national security, and China’s Grand Strategy—factors that have significantly shaped the global order. Through an extensive literature review, the study highlights ethnic conflicts particularly in Xinjiang, serve as a primary driver for China’s Grand Strategy, emphasizing national security and strategic interests. Moreover, the findings suggest that military and economic imperatives play a crucial role in designing this strategy, particularly through the implementation of the Belt and Road Initiative (BRI), which intends to promote regional development and stability in the state. The study demonstrates that ethnic conflicts intensify the state’s focus on national security, influencing key policy-making decisions. Ultimately, it argues that China’s Grand Strategy is designed to ensure both national survival and sustained prosperity.